A new challenge in the Electronics teaching/learning process for the Industrial Design Engineering Bachelor. An interactive educational tutorial - Trujillo-Aguilera, Davinia; Sotorrío-Ruiz, Pedro Juan; Pozo-Ruz, Ana; Martín-Vega, Francisco-Javier (My University, 2015)
Abstract—The adaptation of new curricula to the European Higher Education Area implies a radical change in the teaching/learning process: it is necessary to get students more involved as well as to promote their independence and active participation. The fast-growing technological development, the increasing use of Information and Communication Technologies (ICT) and the advent of e-learning technologies make possible the achievement of this change. It is described a powerful interactive electronics educational tool, which can be embedded in a web page in order to simplify its use by the university students. The results obtained by means of a test demonstrate the benefits of the use of this tutorial and the increase in the motivation students.
Keywords: Enseñanza - Innovaciones tecnológicas; Electrónica - Estudio y enseñanza superior; European Higher Education Area; Interactivity; Electronics; Teaching/learning process; Educational innovation